Novel molecular markers for the detection of methanogens and phylogenetic analyses of methanogenic communities - Dziewit, Lukasz; Pyzik, Adam; Romaniuk, Krzysztof; Sobczak, Adam; Szczesny, Pawel; Lipinski, Leszek; Bartosik, Dariusz; Drewniak, Lukasz (Frontiers in Microbiology, 2015)
Methanogenic Archaea produce approximately one billion tons of methane annually, but their biology remains largely unknown. This is partially due to the large phylogenetic and phenotypic diversity of this group of organisms, which inhabit various anoxic environments including peatlands, freshwater sediments, landfills, anaerobic digesters and the intestinal tracts of ruminants. Research is also hampered by the inability to cultivate methanogenic Archaea. Therefore, biodiversity studies have relied on the use of 16S rRNA and mcrA [encoding the α subunit of the methyl coenzyme M (methyl-CoM) reductase] genes as molecular markers for the detection and phylogenetic analysis of methanogens. Here, we describe four novel molecular markers that should prove useful in the detailed analysis of methanogenic consortia, with a special focus on methylotrophic methanogens. We have developed and validated sets of degenerate PCR primers for the amplification of genes encoding key enzymes involved in methanogenesis: mcrB and mcrG (encoding β and γ subunits of the methyl-CoM reductase, involved in the conversion of methyl-CoM to methane), mtaB (encoding methanol-5-hydroxybenzimidazolylcobamide Co-methyltransferase, catalyzing the conversion of methanol to methyl-CoM) and mtbA (encoding methylated [methylamine-specific corrinoid protein]:coenzyme M methyltransferase, involved in the conversion of mono-, di- and trimethylamine into methyl-CoM). The sensitivity of these primers was verified by high-throughput sequencing of PCR products amplified from DNA isolated from microorganisms present in anaerobic digesters. The selectivity of the markers was analyzed using phylogenetic methods. Our results indicate that the selected markers and the PCR primer sets can be used as specific tools for in-depth diversity analyses of methanogenic consortia.